An Experimental Comparison of Dispute Rates in Alternative Arbitration Systems - Ashenfelter, Orley; Currie, Janet; Farber, Henry S.; Spiegel, Matthew (Econometrica, 1992)
Orley Ashenfelter, Janet Currie, Henry S. Farber, Matthew Spiegel, An Experimental Comparison of Dispute Rates in Alternative Arbitration Systems, Econometrica, Vol. 60, No. 6 (Nov., 1992), pp. 1407-1433